Overview of Social Support for Students Who Work While Studying at the University for Muhammadiyah Sidoarjo: Gambaran Dukungan Sosial pada Mahasiswa yang Bekerja Sambil Kuliah di Universitas Muhammadiyah Sidoarjo - Susanti, Mellya Eka; Maryam, Effy Wardati (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the phenomenon of social support problems in students who work while studying, such as other students who don't care when a friend is having difficulties, lack of empathy among students which causes them to hurt each other both verbally and non-verbally and the high demands of others. old to always get a perfect value without being supported by adequate facilities. This study aims to determine the description of social support for students who work while studying at the Muhammadiyah University of Sidoarjo. This research is a descriptive quantitative research. The variable in this study is social support. This research was conducted at Muhammadiyah University of Sidoarjo with a population of 3,836 students who work while studying. The sample in this study was 320 students who were taken by the Incidental Sampling technique where the determination of the sample was based on chance. The data collection technique in this study used a psychological scale with a Likert scaling model, namely social support. Data analysis was carried out using Corrected item-total correlation which could be done using the SPSS 25.0 for Windows program. The results showed that most of the students who worked while studying were in the medium category with a percentage of 55.6%.